Geostrategic Conjuncture of Commercial and Civil Aviation at Portugal on Early 20th Century - Neves, Fernando M. S. P. (2020)
Aviation Pioneers were, directly and indirectly, responsible for the advancement of flight and other accomplishments in aviation. Due to the advances on the aircraft along WWI, the 1920s was a formative decade in the Aviation, with a major request falling on aerial navigation. In 1921 Gago Coutinho improved the internal means of aerial navigation with an unprecedented precision that consequently led some Portuguese pioneers to perform several trans-Atlantic flights tracking very high accuracy routes. Seeking to take advantage of the Astronavigation accuracy for the benefit of the Geostrategic Conjuncture of Commercial and Civil Aviation at Portugal in the Early 20th Century, Sacadura Cabral encourages the Country for the aviation progress and for the creation of an International Portuguese Airline with inter-Atlantic Portugal-Brazil aerial connections. In 1927, Sarmento de Beires wrote a letter to the President of the Portuguese Republic, explaining all factors of indisputable relevance requesting the attention of the Government in the urgent resolution on Geostrategic Conjuncture of Commercial and Civil Aviation at Portugal. Any positive response from the Portuguese Government to this letter could have resulted in the anticipation of airmail transport between the two continents and a very different Portuguese Aviation History, carrying unpredictably, incalculable and auspicious consequences for Portugal. The historical records in aviation between Europe and South America disclose a first postal flight service in 1934 (7 years later), and commercial passengers flight after WWII.